Numerasi Peserta Didik SMP Ditinjau Dari Kecerdasan Majemuk Dalam Menyelesaikan Soal AKM - Putri, Alifia Rachma; Wijayanti, Pradnyo (Universitas Negeri Surabaya, 2024)
This study aims to describe the numeracy skills of middle school students from the perspective of multiple intelligences in solving AKM (Asesmen Kompetensi Minimum) problems. The research subjects consist of three eighth-grade students from class VIII-C at SMPN 14 Surabaya, who possess linguistic, logical-mathematical, and visual-spatial intelligences. Data collection was conducted through the examination of multiple intelligence questionnaires, mathematics ability tests, AKM problems, and interviews. These interviews were conducted to gain deeper insights into the students' numeracy skills based on their work results. The data analysis was carried out using numeracy indicators, including communication, mathematization, representation, reasoning and argumentation, problem-solving strategy selection, and the use of symbolic, formal, and technical language and operations. The results of the study indicate that students with linguistic intelligence write down the process of reaching solutions, summarize mathematical results both in written and oral forms, convert contextual problems into mathematical forms using difference, percentage, and average formulas, and transform data presented in bar charts into written form. They also use the provided data to solve problems, create patterns and relationships to address issues logically and correctly, determine the appropriate formulas for solving problems, and write down steps or strategies, although not in detail, while using mathematical symbols in calculations. Students with logical-mathematical intelligence demonstrated similar abilities but with more detailed and clearer steps and the use of more symbols. Meanwhile, students with visual-spatial intelligence showed similar abilities but only summarized results orally and did not write down the solution steps in detail.